PERLINDUNGAN HUKUM BAGI ORANG YANG TIDAK CAKAP BERTINDAK SECARA HUKUM TERKAIT DITOLAKNYA IZIN PERALIHAN HAK ATAS TANAH DAN BANGUNAN - Kuspermadi, Raghil Abdul Muqsith; Marniati, Felicitas Sri; Chandra, Tofik Yanuar (Program Studi Hukum Program Pasca Sarjana, 2025)
Legal capacity as a legal subject refers to the ability to possess rights and obligations under the law, thereby granting the authority to act. The transfer of land and building rights owned by individuals who are legally incapacitated must be carried out by a legally authorized representative with prior approval from the court. This research aims to address two key issues: the legal consequences of rejecting the transfer of land and building rights belonging to legally incapacitated individuals, and the legal protection available to them in such cases. The study employs a normative juridical research method, utilizing primary, secondary, and tertiary legal sources. The research approach includes statutory, case law, and analytical methods. Legal materials were gathered through documentation studies, and the legal analysis was conducted using grammatical and systematic legal interpretation. The findings indicate that court approval is essential for appointing a guardian or curator for legally incapacitated individuals, ensuring the protection of their rights. Additionally, the guardian or curator must obtain court approval before transferring or encumbering the land and buildings of the legally incapacitated individual. The court ruling serves as the legal basis for such transactions. It is recommended that parents, guardians, and curators systematically inventory the assets and financial requirements necessary for managing the affairs of legally incapacitated individuals. Furthermore, they should actively advocate for the rights of those under their care by taking appropriate legal measures.